Strategi UNICEF dalam Upaya Menangani Malnutrisi pada Anak di Palestina 2020-2024 - Januari Pratama Nurratri Trisnaningtyas; Desy Puspita Nur Izzah; Maurissa Tiara Putri; Yohana Ajeng Purborini (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research examines UNICEF's strategies to address child malnutrition in Palestine during the period 2020-2024. The background of this research is rooted in the high rate of malnutrition caused by prolonged conflict, limited access to food, and inadequate health services in the region. The main objective of this research is to analyze the effectiveness and challenges faced in the implementation of UNICEF's programs aimed at reducing malnutrition among Palestinian children. To describe in detail the results of UNICEF's implementation in its efforts to address malnutrition in Palestinian children, the author uses the application of the Triple Nexus theory. The method used in this research is qualitative with a literature study approach, which involves secondary data analysis from UNICEF reports, humanitarian organizations, and related scientific publications. The results showed that UNICEF implemented various strategies, including nutritious food distribution, nutrition education to families, and collaboration with local and international partners. Despite improvements in access to aid and nutrition knowledge among communities, challenges such as conflict-induced distribution bottlenecks and limited funding remain key constraints. However, this study confirms that UNICEF's strategy has been effective in reducing malnutrition rates but that broader collaborative efforts and continued support are needed to overcome the obstacles on the ground and ensure the well-being of Palestinian children.